On domestic demand and export performance in the euro area countries: does export concentration matter? - Paulo Soares Esteves; Elvira Prades (European Central Bank (ECB), 2016)
During economic downturns, weak domestic demand developments seem to be an additional driver of exports, as firms increase their efforts to serve markets abroad to compensate the fall in domestic sales. This may constitute an additional mechanism adjustment for the euro area countries where real exchange rate variations are limited by the common currency itself and the present low inflation environment. However, this substitution effect between domestic and foreign sales could be different across euro area members. This paper uses panel data techniques to assess the role of the export structure in explaining these differences. Building a novel indicator for product concentration, the results suggest that domestic demand developments are more relevant to explain exports in countries with a lower product concentration index (that is, more diversified exports). This contributes to explain why euro area countries under stress registered different economic performance during the most recent years.
Keywords: C22; E03; F10; 330; domestic demand pressures; external adjustment